Pharmacokinetic and drug absorption profiles of the anti-hyperglycemic agent gliclazide in oral tissue-targeted-microcapsules - Jović, Jelena; Milijašević, Boris; Vukmirović, Saša; Vasović, Velibor; Mikov, Momir; Mooranian, Armin; Al-Salami, Hani; Goločorbin-Kon, Svetlana (Scripta Medica, 2020)
Background: Gliclazide is one of the most commonly prescribed oral anti-hyperglycemic therapies in Type 2 diabetes mellitus (T2D). Recently reported additional beneficial pharmacological properties of gliclazide, including immunomodulatory and anticoagulant activities, suggested its potential application in treatment of Type 1 diabetes mellitus (T1D). However, following oral administration, gliclazide was shown to have poor and variable absorption directing research into development of novel pharmaceutical delivery systems of gliclazide suitable for T1D. Since bile acids have previously demonstrated stabilizing and controlled-release effects on microcapsules, their use for preparation of microcapsules of gliclazide may lead to improvements in gliclazide release, absorption and antidiabetic effects. Aim: To evaluate drug absorption profiles and hypoglycemic effects of alginate-based microcapsules of gliclazide, prepared together with or without cholic acid, in healthy rats. Methods: Thirty healthy Wistar rats with confirmed normal glucose concentration of in the blood were allocated into five groups and administered with a single dose of either vehicle microcapsules, gliclazide in suspension, gliclazide microcapsules, gliclazide in suspension together with cholic acid or microencapsulated gliclazide in combination with cholic acid. Following respective gliclazide dose, blood was sampled over next 10 hours and blood glucose levels and gliclazide serum concentrations were measured. Results: Our analysis demonstrated altered effects of different gliclazide formulations in healthy rats with the highest gliclazide absorption mirrored by the most profound hypoglycemic effect being achieved after its oral administration as a suspension (p
Keywords: Gliclazide, Capsules, Bile Acids, Hypoglycemic Agents, Rats